Regional settlement system as a basis for the formation of growth poles (case of Kharkiv region) - Kostyantyn Niemets; Kateryna Kravchenko; Anastasiia Mazurova; Kateryna Sehida; Anatoly Lurie (Časopis Socìalʹno-Ekonomìčnoï Geografìï. Часопис соціально-економічної географії, 2018)
The article deals with analysis of population resettlement systems of the Kharkiv region in order to allocate the regional growth poles. The analysis of scientific researches in the field of "center-periphery" theories, the theory of "central places" and the study of the supporting framework of resettlement have been carried out. The works by J. Thünen, W. Christaller, A. Lösch, F. Per-roux, W. Isard, G. Lappo and other authors have been analyzed. Some aspects of the urban study woldwide are presented. The spatial formational aspects of the modern urban settlement system of Kharkiv region are revealed. There are two stages of formation of the regional growth poles. stage I – 16-17 centuries, formation of the supporting framework of population settlement in connection with settlement development of the regional territory; stage II – 19-20 centuries, active economic, industrial development of Kharkiv re-gion. In accordance with the theory of integral systems of resettlement, the diversified organizational cores of the settlement system by population of the Kharkiv region have been determined. The organizational core of the rank 1 is Kharkiv (the central city in the region), 2 rank`s cities are Lozova and Izium (major cities of oblast significance), 3 rank`s cities are Kupiansk, Balakliia, Liubotyn, Pervomaiskyi, (cities with the predominance of industrial and transport functions), 4 rank`s cities are Bohodukhiv, Vovchansk, Zmiiv, Barvinkovo, Nova Vodolaga, Vysokyi, Dergachi (regional agro-industrial centers), 5 rank`s cities are Panyutyne, Kozacha Lopan, Borova (cities and villages that have an important transport position), 6 rank`s cities are Blyzniuky, Vilcha, Chervonyi Oskil, Kolomak, Zachepilovka (villages with high development of agriculture). Problems and perspectives of evolution of the Kharkiv re-gion resettlement system are revealed.